MORPHOLOGICAL FEATURES OF COMPONENTS AND FUNCTIONAL PARAMETERS OF SYNOVIAL SHELL OF RATS - Pelypenko, O.V.; Shepitko, V.I. (World of Medicine and Biology, 2018)
The presence of chronic joint disease is a common cause of a doctor’s visits with complaints of intermittent pain or a presents of discomfort or achiness in the joints when moving or at rest. Osteoarthritis – a disease that is spread throughout the world. The reasons for its development are quite diverse.Previously, scientists explained the cause of this disease only by changes in cartilaginous tissues. At the present time, awareness of the occurrence of complex changes of all components of the joint predominates [2,6].The synovial sheath of a joint performs a number of functions that ensure the normal functioning of a joint under normal conditions, with various loads and with the occurrence of pathological changes locally in the joint and in the body as a whole [7,9]. The similarity of the morphological structure of the synovial membrane of man and small animals makes it possible to conclude that the data of experimental studies are reliable when using white rats [5,8]. Data for the normal values of the cellular composition of the synovial membrane in experimental studies are quite limited [1,3].The similarities of the structure of the vascular bed of any life tissue are given to the scientists attention because the given structure is the predominant source of life of the environment, an indicator of the general processes to which the body is being adapted after multiple external factors [4,10].The purpose of the study was to determine the morphological characteristics of the synovial membrane structures of the knee joints of the rats to further compare them with the development of pathological changes in the joint, mainly inflammatory, and after the application of therapeutic measures.The total of 30 rats of the “Wistar” line at the age of 12 weeks weighing 130-150 g were used in the study. Experiments on animals were carried out in accordance with the rules of the European Convention on Human Behavior in Animals.Distal metaphysis of femoral bones, which were used for histological examination, were fixed with 10% neutral formalin, after which decalcification? (decalcination) of bone tissue was performed. The cuts obtained on the microtome were stained with hematoxylin and eosin. Material study was carried out using Biorex-3 VM-500T microscope with digital micro protection DCM 900 with adapted data research programs.In the synovial membrane, the coating sheath, the deep and superficial collagen-elastic sheaths were isolated.The cells of the cover membrane are not well-oriented, their construction is so disorganized that it is sometimes not a subject to systematic description. There is no basement membrane separated covering cells from the matrix and asynchronously located synoviocytes.Synoviocytes of the cover layer are characterized by large size, the presence of a significant amount of microvilli, which evidenced by their ability and secretory activity and phagocyte function. The coating layer is the main substance of intense metabolic processes between the articular cavity and articular capsule layers. The development of the pathological process is primarily localized in the cover layer of the synovial membrane.A vector orientation of the location of collagen fibers, both surface and deep collagen-elastic layers of the synovial membrane, was noted. Angular deviations in the direction of morphological structures were quite variable (from 90º to 140º), depending on the location of a taken material.The thick collagen-elastic layer was prevalent. In both layers, there were fibroblasts, individual macrophages (mainly in the deep layer) and mast cells. Dense location of collagen fibers was noted and the synchronous loopiness of elastic fibers corresponding their vectoral orientation.The superficial layer of blood vessels was represented by fairly wide range of capillaries, which were located at a little depth from the surface of the synovial membrane. Uneven location and diameter of the vessels with their predominant localization at the base of synovial fibers and places of dilution of the collagen-elastic layer was noted. The main capillary complex in the form of a mesh structure located in the immediate proximity to the thinned layer of synoviocytes cells.A large number of arteriovenous anastomoses are observed at the base of synovial villi. In the deep layer of blood vessels, prevalent venous component over the arterial, both in the ratio and in the volume of 1:2 due to the formation of inter venular anastomoses and venous gaps which were observed.Particular attention was paid to the lymphatic system. A significant number of lymphatic capillaries, which began blindly had a fairly diverse diameter and length, although they were often localized in the area of vascular accumulation, which describe them as active participants in the metabolic processes. The performed study has proved that the synovial membrane of rats has a complex spatial and qualitative structure, the components of which are in close relationship with each other. Individual differences in morphological characteristics should be taken into consideration in scientific research with subsequent interpretation of certain relationships in laboratory and clinical experiments.
Keywords: knee; synovial membrane; rats